In vivo hypoxia and a fungal alcohol dehydrogenase influence the pathogenesis of invasive pulmonary aspergillosis. - Nora Grahl; Srisombat Puttikamonkul; Jeffrey M Macdonald; Michael P Gamcsik; Lisa Y Ngo; Tobias M Hohl; Robert A Cramer (PLoS Pathogens)
Currently, our knowledge of how pathogenic fungi grow in mammalian host environments is limited. Using a chemotherapeutic murine model of invasive pulmonary aspergillosis (IPA) and (1)H-NMR metabolomics, we detected ethanol in the lungs of mice infected with Aspergillus fumigatus. This result suggests that A. fumigatus is exposed to oxygen depleted microenvironments during infection. To test this hypothesis, we utilized a chemical hypoxia detection agent, pimonidazole hydrochloride, in three immunologically distinct murine models of IPA (chemotherapeutic, X-CGD, and corticosteroid). In all three IPA murine models, hypoxia was observed during the course of infection. We next tested the hypothesis that production of ethanol in vivo by the fungus is involved in hypoxia adaptation and fungal pathogenesis. Ethanol deficient A. fumigatus strains showed no growth defects in hypoxia and were able to cause wild type levels of mortality in all 3 murine models. However, lung immunohistopathology and flow cytometry analyses revealed an increase in the inflammatory response in mice infected with an alcohol dehydrogenase null mutant strain that corresponded with a reduction in fungal burden. Consequently, in this study we present the first in vivo observations that hypoxic microenvironments occur during a pulmonary invasive fungal infection and observe that a fungal alcohol dehydrogenase influences fungal pathogenesis in the lung. Thus, environmental conditions encountered by invading pathogenic fungi may result in substantial fungal metabolism changes that influence subsequent host immune responses.